2009
DOI: 10.1530/eje-08-0840
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic variance of corticotropin affects diagnosis in adrenal vein sampling

Abstract: Objective: Differentiating unilateral form from bilateral is a critical diagnostic step in primary aldosteronism (PA), for which adrenal vein sampling (AVS) is accepted to be the most reliable. However, variance of corticotropin could affect the diagnosis in AVS. Design and methods: We conducted simultaneous bilateral AVS on ten biochemically diagnosed PA cases, and used the aldosterone-to-cortisol ratio (A/C) of the samples for the diagnosis. The diagnosis by AVS after a low-dose (0.1 mg) ACTH stimulation, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
2
20
0
1
Order By: Relevance
“…In agreement with emerging findings from other groups, 5,6,13,14 the above considerations conversely imply that cortisol provides a less than optimal parameter to establish selective catheterization in nonstimulated sequential AVS procedures. This conclusion is reinforced by our findings that metanephrine to normetanephrine and epinephrine to norepinephrine ratios in most nonstimulated AV samples designated nonselective, based on a cortisol-derived selectivity index of 3.0, were well above the range for ratios in PV samples and within the range for the AV samples designated as selective.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In agreement with emerging findings from other groups, 5,6,13,14 the above considerations conversely imply that cortisol provides a less than optimal parameter to establish selective catheterization in nonstimulated sequential AVS procedures. This conclusion is reinforced by our findings that metanephrine to normetanephrine and epinephrine to norepinephrine ratios in most nonstimulated AV samples designated nonselective, based on a cortisol-derived selectivity index of 3.0, were well above the range for ratios in PV samples and within the range for the AV samples designated as selective.…”
Section: Discussionsupporting
confidence: 86%
“…First, as demonstrated by others, [4][5][6] adrenal secretion of cortisol fluctuates so that AV plasma concentrations during periods of low secretion may be only slightly higher than those in peripheral plasma, providing the rationale for cosyntropin stimulation. In contrast, metanephrine is produced continuously within adrenal medullary cells from epinephrine leaking from storage vesicles, a process that is independent of fluctuations in epinephrine release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the advantages of ACTH 1-24 infusion may be a higher step up between peripheral and adrenal vein cortisol values and thus a higher percentage of successful studies. However, the effects on lateralization and thus on diagnosis are not that clear-cut: in a relatively small study with ten patients undergoing AVS first without and then with ACTH 1-24 infusion the authors noted a lateralization toward the wrong side for the values sampled at baseline, suggesting that concomitant ACTH 1-24 infusion might increase the diagnostic reliability (17). A larger study comparing baseline with bolus and continuous infusion of ACTH 1-24 found a completely different effect, claiming that ACTH 1-24 infusion improved the percentage of successful samplings but reduced the number of correctly diagnosed APAs (18).…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the impact of these factors, ACTH infusion was introduced by Weinberger et al (22) and widely used thereafter (21,23,24), thus being held as an essential part of the sequential AVS (11,19,21,25), or even of bilaterally simultaneous AVS (5,26,27). In our hands, cosyntropin stimulation confounded the assessment of lateralization and led to misclassification of the APA side (8,17).…”
Section: Impact Of Sequential or Simultaneous Avs On Si Valuementioning
confidence: 80%